The Effect Of Current Ratio, Company Size, Return On Asset And Debt To Equity Ratio On Profit Growth On Consumer Goods Companies Listed On The Indonesia Stock Exchange 2018 – 2020 - Jessica; Kevin Wiguna Chandra; Robin; Lenta Friska Purba (Jurnal Mantik, 2022)
This study analyzes the effect of CR, firm size, ROA, and DER on profit growth in IDX consumer product companies 2018-2020. This research is quantitative. The sampling approach was purposive sampling, using 34 consumer goods businesses listed on the Indonesia Stock Exchange in 2018-2020 multiplied by 3 years during the research period. Research using multiple linear regression shows that CR, company size, ROA, and DER have a simultaneous and substantial effect on profit growth in consumer product companies listed on the Indonesia Stock Exchange 2018 - 2020. CR has a small effect on profit growth in the consumer business. . listed on the IDX 2018 - 2020. Company size has no effect on profit growth in consumer goods companies listed on the IDX 2018-2020. ROA affects profit growth in the NYSE consumer goods business. Indonesia Stock Exchange 2018-20. DER has little effect on the consumer product business listed on the Indonesia Stock Exchange on 2018-2020 profit growth